M6GP - Batista, João Eduardo (2024)
Batista, J. E., Rodrigues, N. M., Vanneschi, L., & Silva, S. (2024). M6GP: Multiobjective Feature Engineering. In 2024 IEEE Congress on Evolutionary Computation (CEC) (pp. 1-8). Institute of Electrical and Electronics Engineers (IEEE). https://doi.org/10.1109/CEC60901.2024.10612107 --- This work was supported by FCT through the LASIGE (UIDB/00408/20203 and UIDP/00408/20204) and MagIC/NOVA IMS (UIDB/04l52/2020) research units, and PhD Grant 202l/05322/BD